PENGARUH JENIS BAHAN ORGANIK TERHADAP PERTUMBUHAN DAN HASIL DUA VARIETAS TOMAT (Lycopersicum esculentum Mill L.) - Agustina Agustina; Jumini Jumini; Nurhayati Nurhayati (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2015)
This study was aimed at determining type of organic material suitable for the growth and yield of two varieties of tomatoes and the interaction between the two factors. This experiment was conducted at the experimental field of the Agriculture Faculty, Syiah Kuala University, Darussalam, Banda Aceh. The experiment was arranged in a randomized complete block design, 4 x 2 with three replications. There were two factors investigated: organic material consisting 4 levels (control, manure, compost peat, and compost), varieties consisting two levels (Permata and Lentana F1). Variables observed were height and stem diameter, fruit weight per plant, number of fruits per plant, number of bunches per plant, number of fruits per bunch, average weight per fruit and yield potential. The results showed that the type of organic material highly significantly affected plant height and stem diameter at the ages of 30 and 45 days after planting, fruit weight per plant, number of fruits per plant, and significantly affected plant height at the age of 15 HST but did not significantly affect the number of bunches per plant, number of fruits per bunch, average weight per fruit and yield potential. Growth and yield were better at manure compared to compost, peat compost, and control. Varieties significantly affected stem diameter at the age of 15, 30 and 45 days after planting, fruit weight per plant, number of fruits per plant, number of bunches per plant, number of fruits per bunch, average weight per fruit and potential results. Growth and yield were better found in varieties Permata. There were significant interactions between types of organic materials and varieties in all observed variables on growth and yield of tomato.